Climate Change Marches as Motivators for Bystander Collective Action - Swim, Janet K.; Geiger, Nathaniel; Lengieza, Michael L. (Frontiers in Communication, 2019)
Political marches are one of the most public and vocal means of engaging in collective action and can potentially build social movements by increasing the likelihood that bystanders become engaged with the social movement. Here, we conduct a trend study to test the impacts of two back-to-back highly visible large-scale climate change related marches on bystanders, targeting psychological drivers of collective action: efficacy beliefs, perceptions of others’ climate change activism and concerns, impressions of marchers, and behavioral intentions. Participants either completed a survey the day before the March for Science (n = 302) or several days after the People’s Climate March, which occurred a week after the first march (n = 285). Results suggest that the marches were at least partially effective: bystanders’ a) collective efficacy beliefs and b) impressions of marchers improved after the march. In contrast, marches were ineffective in increasing perceptions of others’ engagement with concern about climate change. We anticipated that political leaning of bystanders’ news sources would moderate effects of marches. An unanticipated effect was improved collective efficacy beliefs among consumers of conservative, but not liberal, news. This unanticipated result is consistent with the notion that conservative news sources dedicated less coverage than liberal news sources to the marches prior to the marches (potentially leading to lower collective efficacy among those who consumed these sources), but that coverage afterwards was more equal across ideological bias of news sources. We also found that the more conservative the news sources consumed by an individual, the more negative impressions they had of marchers, and this relation was strongest among those that indicated, after the marches, that they had heard about the marches. These results on impressions are consistent with the notion that, when marches were covered, conservative news sources portrayed relatively more negative portrayals than liberal news sources. Overall, results suggest that marches can increase the likelihood that bystanders will participate in social movements via changes in psychological drivers of participation and the effects will likely depend upon political leanings of news sources via both whether sources mention the marches and how the sources cover about the marches.